Definitions of Resistant and Refractory Cytomegalovirus Infection and Disease in Transplant Recipients for Use in Clinical Trials. (22nd August 2018) - Chemaly, Roy F; Chou, Sunwen; Einsele, Hermann; Griffiths, Paul; Avery, Robin; Razonable, Raymund R; Mullane, Kathleen M; Kotton, Camille; Lundgren, Jens; Komatsu, Takashi E; Lischka, Peter; Josephson, Filip; et al.
Abstract : Standardized consensus definitions for resistant and refractory cytomegalovirus (CMV) infections and diseases in transplant recipients were developed by the CMV Resistance Working Group of the CMV Drug Development Forum and are intended to be used in clinical trials. Abstract: Despite advances in preventive strategies, cytomegalovirus (CMV) infection remains a major complication in solid organ and hematopoietic cell transplant recipients. CMV infection may fail to respond to commercially available antiviral therapies, with or without demonstrating genotypic mutation(s) known to be associated with resistance to these therapies. This lack of response has been termed "resistant/refractory CMV" and is a key focus of clinical trials of some investigational antiviral agents. To provide consistent criteria for future clinical trials and outcomes research, the CMV Resistance Working Group of the CMV Drug Development Forum (consisting of scientists, clinicians, regulatory officials, and industry representatives from the United States, Canada, and Europe) has undertaken establishing standardized consensus definitions of "resistant" and "refractory" CMV. These definitions have emerged from the Working Group's review of the available virologic and clinical literature and will be subject to reassessment and modification based on results of future studies.